2008
DOI: 10.1111/j.1749-4877.2008.00070.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil type limits population abundance of rodents in crop fields: case study of the multimammate rat Mastomys natalensis Smith, 1834 in Tanzania

Abstract: Studies of populations of the multimammate rat Mastomys natalensis in Morogoro, Tanzania, show that soil texture appears to influence the population abundance and distribution of these rats in agricultural fields. The lowest rodent population abundance was found on sandy clay soils (F (2, 5) = 8.42; P = 0.025). The population abundances of M. natalensis on sandy clay loam and sandy loam soils did not differ significantly (P ≤ 0.05), possibly because these soils have a very similar texture. The results of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 4 publications
0
12
2
Order By: Relevance
“…The ecology of rodent pests in agro-ecosystems has been studied in many parts of Africa (Leirs and Verheyen 1995;Monadjem 1998;Massawe et al 2008;Makundi et al 2010), and an elaborate model forecasting Mastomys outbreaks in Tanzania has been developed (Leirs et al 1996a). All these studies, however, have focused on rodents either in crop fields or in edge habitat between fields and natural vegetation.…”
mentioning
confidence: 99%
“…The ecology of rodent pests in agro-ecosystems has been studied in many parts of Africa (Leirs and Verheyen 1995;Monadjem 1998;Massawe et al 2008;Makundi et al 2010), and an elaborate model forecasting Mastomys outbreaks in Tanzania has been developed (Leirs et al 1996a). All these studies, however, have focused on rodents either in crop fields or in edge habitat between fields and natural vegetation.…”
mentioning
confidence: 99%
“…Indeed, sandy loam soils have been associated with supporting a variety of vegetative plants which offer food and cover to the rodents thus increasing survival and recruitment (Leirs et al 1990, Mulungu et al 2016. It has been demonstrated that sandy loamy soils have good aeration and are friable making them easier for the animals to burrow in (Massawe et al 2008, Meliyo et al 2015).…”
Section: Small Rodent Abundancementioning
confidence: 99%
“…Among the different pests, rodents are responsible for a significant amount of pre-and post-harvest losses particularly to cereal crops in Uganda and the rest of East African region (Leirs et al 1997, Makundi et al 2006, Mulungu et al 2010, Mayamba et al 2019. Their distribution and abundance have been shown to vary temporally and spatially due to different ecological factors including land use/land cover types (Fraschina et al 2014, Hieronimo et al 2014, soil properties (Massawe et al 2008, Meliyo et al 2015 climate (Leirs et al 1997), and land management practices (Massawe et al 2007, Hieronimo et al 2014. For instance, the Normalized Difference Vegetation Index (NDVI), a remote sensing based proxy indicating the greenness of the vegetation in an area, has been demonstrated to be the most important predictor of small rodent species richness and abundance in a semi-arid climate in Tanzania (Chidodo 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although known as an opportunistic species able to occupy a wide range of habitats, several natural environment factors nonetheless limit the spatial distribution of M. natalensis. The type of soil appears important, with higher abundance observed in regions with high vegetation cover and sandy (Massawe et al, 2005(Massawe et al, , 2008. Both these environmental factors can be naturally and anthropogenically determined, thus farming practice and land use are also likely to affect the population biology of the rodent .…”
Section: Lassa Fevermentioning
confidence: 99%